Brain Organoids as Tools for Modeling Human Neurodevelopmental Disorders - Adams, Jason W. (Physiology (Bethesda), 2019)
Brain organoids recapitulate in vitro the specific stages of in vivo human brain development, thus offering an innovative tool by which to model human neurodevelopmental disease. We review here how brain organoids have been used to study neurodevelopmental disease and consider their potential for both technological advancement and therapeutic development.